Scaphoid Nonunion With Poor Prognostic Factors: The Role of the Free Medial Femoral Condyle Vascularized Bone Graft. (March 2017) - Chaudhry, Tahseen; Uppal, Lauren; Power, Dominic; Craigen, Michael; Tan, Simon
Background: To report on the results of free medial femoral condyle (MFC) vascularized bone graft for scaphoid nonunions with 1 or more poor prognostic factors.Methods: We have used the free MFC vascularized bone graft for scaphoid nonunions that have 1 or more factors associated with a poor prognosis. These were, a delay in presentation of over 5 years, a proximal pole nonunion, the presence of avascular necrosis (AVN), or previous nonunion surgery. We used this technique on 20 patients over a 4.5-year period.Results: Our overall union rate was 88.5% (17 of 19 patients), with 1 patient failing to attend for follow-up. Our mean union time was 7 months (2-18). All patients had at least 1 poor prognostic factor and over half had 2 or more. Of those with AVN with or without other factors, the union rate was 85% (11 of 13). There were 2 donor site complications that required a further procedure and 2 patients with residual wrist pain that required a scapho-trapezio-trapezoid joint fusion and a radial styloidectomy, respectively. Both nonunions were offered further surgery, and 1 elected to undergo successful revision surgery.Conclusions: Overall, this technique showed good results, in a subgroup of patients that typically have poorer outcomes, with a low incidence of donor site morbidity. Our union rate compares favorably with other techniques for this difficult subset of patients with 1 or more poor prognostic factors, although results are clearly not as good as those of studies using the MFC graft for all scaphoid nonunions. We continue to reserve this technique for nonunions with 1 or more poor prognostic factors, and we believe that this technique should at least be considered in these patients.